A semi-analytical time-domain model with explicit fluid force expressions for streamwise fluidelastic instability of a single and multiple flexible tube array - Zhao, Xielin; Sun, Pan; Zhou, Jinxiong (Physics of fluids (1994), 2024)
Fluidelastic instability (FEI) within steam generator tube arrays poses a significant safety concern for nuclear power plants. Traditionally assumed to manifest in the transverse direction, recent failures at the San Onofre Nuclear Generating Station have underscored the importance of understanding streamwise FEI (SFEI). These incidents have spurred analytical investigations into SFEI, but progress has been hindered by the lack of explicit fluid force formulations, particularly in semi-analytical SFEI models. This paper presents a novel semi-analytical time-domain SFEI model featuring an ideal geometry-based decay function and meticulously derived explicit fluid elastic force expressions. The proposed model supports both frequency-domain stability analysis and true time-domain response analysis, and it is applicable to configurations featuring either a single elastic tube in a rigid array or multiple flexible tubes in an array. Additionally, the tube motion phases are obtained by comparing time-domain responses and employing modified multi-tube frequency-domain SFEI analyses. The stability thresholds predicted for a parallel triangular array using our theoretical model closely align with reported experimental data, thereby validating its accuracy. Our work supplements and advances semi-analytical modeling, alleviating implementation challenges for analyzing SFEI phenomena.